Effects of chronodisruption and alcohol consumption on gene expression in reward-related brain areas in female rats - Christiane Meyer; Konrad Schoettner; Shimon Amir (Frontiers in Molecular Neuroscience)
Circadian dysfunction caused by exposure to aberrant light–dark conditions is associated with abnormal alcohol consumption in humans and animal models. Changes in drinking behavior have been linked to alterations in clock gene expression in reward-related brain areas, which could be attributed to either the effect of chronodisruption or alcohol. To date, however, the combinatory effect of circadian disruption and alcohol on brain functions is less understood. Moreover, despite known sex differences in alcohol drinking behavior, most research has been carried out on male subjects only, and therefore implications for females remain unclear. To address this gap, adult female rats housed under an 11 h/11 h light–dark cycle (LD22) or standard light conditions (LD24, 12 h/12 h light–dark) were given access to an intermittent alcohol drinking protocol (IA20%) to assess the impact on gene expression in brain areas implicated in alcohol consumption and reward: the prefrontal cortex (PFC), nucleus accumbens (NAc), and dorsal striatum (DS). mRNA expression of core clock genes (Bmal1, Clock, Per2), sex hormone receptors (ERβ, PR), glutamate receptors (mGluR5, GluN2B), a calcium-activated channel (Kcnn2), and an inflammatory cytokine (TNF-α) were measured at two-time points relative to the locomotor activity cycle. Housing under LD22 did not affect alcohol intake but significantly disrupted circadian activity rhythms and reduced locomotion. Significant changes in the expression of Bmal1, ERβ, and TNF-α were primarily related to the aberrant light conditions, whereas changes in Per2 and PR expression were associated with the effect of alcohol. Collectively, these results indicate that disruption of circadian rhythms and/or intermittent alcohol exposure have distinct effects on gene expression in the female brain, which may have implications for the regulation of alcohol drinking, addiction, and, ultimately, brain health.